Quasi-experimental study on Aloe Vera Gel As A Phytotherapy to Accelerate Perineal Wound Regeneration In Postpartum Mothers At Bpm Pera - Basaria Manurung; Retno Wahyuni; Hariati Eliana Purba; Isyos Sari Sembiring; Eva Ratna Dewi; Nopalina Suyanti Damanik; Titis Jernih Wati Gea (Jurnal Teknokes, 2025)
Perineal wounds are one of the most common complications in postpartum women, causing pain, increasing the risk of infection, and delaying recovery. The lack of effective, safe, affordable, and easily accessible therapies highlights a gap in perineal wound care practices, particularly in primary care. Aloe vera, which contains anti-inflammatory compounds and regenerative bioactives, has the potential to serve as an alternative phytotherapy, but clinical evidence of its effectiveness in perineal wounds remains limited. This study aimed to evaluate the effectiveness of aloe vera gel in accelerating perineal wound healing in postpartum women. The contribution of this research is to strengthen the practice of phytotherapy-based wound care that is safe, affordable, and applicable in primary health care facilities. The study used a quasi-experimental pre-post study design with a control group. Thirty postpartum women with grade I–II perineal wounds were divided into a treatment group (Aloe vera) and a control group (standard care). Healing was evaluated using the REEDA scale, and pain intensity was assessed using a Visual Analogue Scale (VAS) over seven days. Analysis was performed using an independent t-test with a significance level of 0.05. The results showed a significant difference between the two groups. The average healing time for the Aloe vera group was 4.20 days (SD 0.95), faster than the control group, which took an average of 7.00 days (SD 1.20). Statistical tests showed a p-value = 0.001, indicating significant effectiveness of Aloe vera application in accelerating tissue healing. In addition, REEDA and VAS scores on the seventh day were consistently lower in the treatment group, indicating a faster reduction in inflammation and pain. Implicitly, these findings provide a clinical contribution to strengthening safe and affordable phytotherapy-based wound care practices for postpartum mothers, particularly in primary healthcare facilities. This study concluded that aloe vera gel is an effective complementary therapy for accelerating perineal wound healing and improving maternal comfort.